El control de convencionalidad y la protección del derecho a la propiedad privada a partir de la sentencia del caso Salvador Chiriboga vs. Ecuador (Tema Central) - Jácome Ordóñez, María del Carmen (2014)
The contents of this article analyze the right to private property after the decision of the Inter-American Court of Human Rights in the case “Salvador Chiriboga vs. Ecuador”. The author´s concern is the fact that this case represents the most expensive sentence inside the Inter-American protection system due to the violation of the right to private property (art. 21.2 AC); judicial guarantees (art. 8.1 AC) and judicial protection (art. 25.1 CA). This subject has special relevance since Ecuador is facing a judicial reform process and it is necessary to consider that the diffusion of this decision among judges could prevent the commission of the same mistakes; specially, those related to denial of justice as it occurred in the present case study.